The history of flight : we saw it happen [videorecording (DVD)] - Boeing, Bill, Jr., 1922-2015; Grumman, Leroy; Lockheed, Allan, Jr; Martin, Glenn L. (Restored classics, the Film Detective archive., 2020)
A 1953 documentary that was used by United Aircraft to celebrate fifty years of flight and explores aviation like never before with interviews from notable pioneers.